AN INVESTIGATION OF LIQUID METAL AND GAS FLOW CHARACTERISTICS IN CONFINED ATOMIZATION NOZZLE - Ihsan Y. Hussain (Journal of Engineering, 2005)
Supersonic gas jets in confined liquid metal atomizing nozzle were studied by using the method of characteristics. Nitrogen at operation (stagnation) pressure of (1.65Mpa) was used in the study, with three different values of ambient pressure (1.25, 1.52 and 1.75 bar). For all the three values, the nozzle is over expanded. The Mach number at the nozzle exit for all the investigated cases was (2.64). The pressure and Mach number of the atomizing gas at various lattice points downstream of the nozzle exit were found. Besides, the effect of heat transfer from the liquid metal (aluminum) on the gas flow behavior was also investigated, The results showed that the stagnation temperature rise of nitrogen caused by heat transferred from aluminum is very small and can be neglected, and hence the flow can be assumed to be adiabatic. The results indicates that the pressure of the atomizing gas tries to adjust to the higher ambient pressure by the formation of a weak oblique "lip" shock followed by a reflected weak oblique "edge" shock. As the ambient pressure increases, the inward earvature of the jet boundary increases and hence the length of the jet decreases. As the ambient pressure increases, the point at which the oblique "lip" shock strikes the wall moves upstream toward the nozzle exit. If the shock is to be avoided, the difference between the ambient and nozzle exit pressures must be decreased. For fixed nozzle geometry, this can be done either by increasing